2008
DOI: 10.1212/01.wnl.0000307750.41970.d9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of cerebral microbleeds

Abstract: The prevalence of cerebral microbleeds is high. Our data support the hypothesis that strictly lobar microbleeds are related to cerebral amyloid angiopathy, whereas microbleeds in a deep or infratentorial location result from hypertensive or atherosclerotic microangiopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
716
17
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 747 publications
(793 citation statements)
references
References 38 publications
51
716
17
9
Order By: Relevance
“…17 Cortico-subcortical areas are preferentially affected by MBs in accordance with the distribution of Aβ deposition in vascular walls in patients with CAA. [17][18][19] Deep or infratentorial MBs were positively correlated with CAApathology negative in the present study. A previous study suggested that deep or infratentorial MBs are relevant to cardiovascular risk factors, the presence of lacunar infarcts, white matter lesions, and underlying hypertension.…”
Section: Brain Images and Photomicrographs Of Evacuated Hematoma Ansupporting
confidence: 49%
“…17 Cortico-subcortical areas are preferentially affected by MBs in accordance with the distribution of Aβ deposition in vascular walls in patients with CAA. [17][18][19] Deep or infratentorial MBs were positively correlated with CAApathology negative in the present study. A previous study suggested that deep or infratentorial MBs are relevant to cardiovascular risk factors, the presence of lacunar infarcts, white matter lesions, and underlying hypertension.…”
Section: Brain Images and Photomicrographs Of Evacuated Hematoma Ansupporting
confidence: 49%
“…ICH can be divided into primary ICH (PICH) and secondary ICH. PICH accounts for 78%-88% of ICH cases and is mainly caused by chronic hypertension and spontaneous small vessel rupture due to amyloid angiopathy (CAA) [94] .…”
Section: Hemorrhagic Strokementioning
confidence: 99%
“…The differences in age and disease prevalence between earlier studies and ours may have also influenced these results. Indeed, incidence of CMBs increases with age (Vernooij et al., 2008). In addition, the prevalence and number of CMB are relatively high in patients with AD, MCI, and VaD (Cordonnier et al., 2006; Shams et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Strictly lobar CMBs (SL‐CMBs) are thought to be caused by cerebral amyloid angiopathy (CAA) frequently in patients with Alzheimer's disease (AD), whereas nonlobar CMBs (deep or infratentorial) are thought to be due to hypertensive vasculopathy (HV) (Greenberg et al., 2009; van Rooden et al., 2009). Mixed (deep/infratentorial with lobar) CMBs (M‐CMBs) are also thought to reflect HV (Greenberg et al., 2009; Vernooij et al., 2008). HV and CAA may synergistically contribute to the development of lobar CMBs (Cordonnier & van der Flier, 2011; Fazekas et al., 1999; Kim et al., 2016; Lee, Kim, Kim, Yoon, & Roh, 2007; Park et al., 2013; Smith et al., 2010).…”
Section: Introductionmentioning
confidence: 99%